ANALISIS YURIDIS TERHADAP PEREMPUAN SEBAGAI KORBAN PERDAGANGAN MANUSIA DALAM PEREDARAN GELAP NARKOTIKA DI INDONESIA - Sembiring, Damenta; Deliana, Evi; ', Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
In the European continent, especially Britain, human trafficking andslavery began with the conquest of the British state to several countries outsidethe European continent. Slavery or servitude has existed in the history of theIndonesian nation. In the days of previous kings, women were a complementarypart of the feudal system of government. In the era of globalization, slavery is rifein its illegal and veiled form in the form of trafficking in women. Women areemployed in dangerous sectors, forbidden work, for forced labor, victims ofsexual exploitation in pornography, prostitution and the most attention is made asdrug couriers. Women do not know that the work that they do does often have todeal with the law even though the women involved are only victims of a crime.The type of research used by researchers is normative juridical legalresearch or can also be called doctrinal legal research. Normative legal researchis a literature study of legal studies. In this normative research the law isconceptualized as what is written in the legislation (law in books) or also the lawis conceptualized as a rule or norm which is a standard of human behavior that isdeemed appropriate. In this study researchers conducted research on theprinciples of law, by way of making prior identification of the legal principles thathave been formulated in the legislation. This study utilizes descriptive methods.The results of this thesis research, it can be seen that women's traffickingis closely related to narcotics crime. The main finding in this study is one of themost prominent patterns in narcotics distribution is the use of women as one ofthe links, especially as narcotics couriers. The existence of women in the narcoticstrade is a chain of trafficking in women that at first glance does not appear(invisible) and is difficult to identify if it does not critically study it. For thisreason, in the legal process and law enforcement against a criminal act,especially in this research must be careful to realize justice for women victims.Suggestions in this thesis research considering that there are still manyinvitations found that are discriminatory against women in the framework of theirlegal protection, it is suggested that a revision of the Law be made. Finally, inorder to break the chain of trafficking in women, especially in the form ofnarcotics circulation must require mutual concern and be the responsibility of allparties, because it concerns the future of the future generation.Keywords : Trafficking of Women - Victims – Justice